2020
DOI: 10.5222/mmj.2020.88614
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Depressive Symptoms in Doctors Working at COVID-19 Hospitals: An Online Survey.

Abstract: Objective COVID19 outbreak has put a tremendous physical and mental burden on frontline doctors. A limited amount of literature is available in this area. The present study was done to assess the depressive symptoms and depression levels in doctors working at COVID-19 Hospitals. Method This study was based on an online survey that was started on May 2020 and ended on 30 th June, 2020. An online questionnaire which included details such as age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The BDI-II is a 21-item self-report measure (Beck et al, 1996 ) that assesses depressive symptoms. The BDI-II has been used in several COVID-19-related studies (Bashir et al, 2020 ; Leão et al, 2023 ; Zabel et al, 2023 ). Items are scored on a Likert scale from 0 to 4, with higher scores specifying more depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The BDI-II is a 21-item self-report measure (Beck et al, 1996 ) that assesses depressive symptoms. The BDI-II has been used in several COVID-19-related studies (Bashir et al, 2020 ; Leão et al, 2023 ; Zabel et al, 2023 ). Items are scored on a Likert scale from 0 to 4, with higher scores specifying more depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…From 65 regions 389 doctors were assessed through an online survey schedule including depression, and hopelessness scales. The findings revealed that among Pakistan's doctors working in emergency departments, there was a 43% predominance of hopelessness/depression, with nearly 94% feeling unprotected (Bashir, et al 2020).…”
Section: Introductionmentioning
confidence: 98%